2021
DOI: 10.1590/0034-7167-2019-0599
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of mobile applications in pregnant women's adherence to prenatal consultations: randomized clinical trial

Abstract: Objective: to evaluate the effectiveness of a mobile application for cell phones in the adherence of pregnant women to prenatal consultations. Method: a randomized controlled clinical trial, simple-blind with two parallel groups, conducted from January to December 2018. Data collection was carried out through a structured interview at the end of the third trimester of pregnancy. For analysis, Chi-Square and Mann-Whitney tests were used. The sample consisted of 88 pregnant women from 2 Family Health Strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Out of 27 studies that were included, 15 (56%) of them were conducted in Africa, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] nine were from Asia, 33,[38][39][40][41][42][43][44][45] two were from South America, 46,47 and one Australia/Oceania. 48 The other six studies were from six countries, Zanzibar, Nigeria, Samoa, Guinea, Bangladesh, and Myanmar, each contributing one.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Out of 27 studies that were included, 15 (56%) of them were conducted in Africa, [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] nine were from Asia, 33,[38][39][40][41][42][43][44][45] two were from South America, 46,47 and one Australia/Oceania. 48 The other six studies were from six countries, Zanzibar, Nigeria, Samoa, Guinea, Bangladesh, and Myanmar, each contributing one.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Marko et al [48] performed a prospective controlled trial and demonstrated that a mobile prenatal-care app reduced the number of in-person visits without decreasing patient satisfaction. Many prenatal mobile apps contain similar information about routine prenatal tests and currently have additional functions, such as coaching for blood sugar control in patients with gestational diabetes, thereby contributing to improving society by improving the lives of pregnant women and even helping their mental health [49][50][51][52][53][54][55].…”
Section: The Effect Of Digital Technologies In Pregnancymentioning
confidence: 99%
“…Pregnant women who used the application attended a greater number of consultations when compared to nonusers. The application showed to be an effective health technology to improve adherence to prenatal care [12]. Similarly, Sultan Özkan Şat et al2021 conducted a crosssectional study on the use of mobile applications by pregnant women and levels of pregnancy distress during the coronavirus pandemic.…”
Section: Limitations Of the Studymentioning
confidence: 99%